The Role of Halogens in Terrestrial and Extraterrestrial Geochemical Processes Surface, Crust, and Mantle (Springer Geochemistry,, 2018)
The book summarizes the knowledge and experiences concerning the role of halogens during various geochemical processes, such as diagenesis, ore-formation, magma evolution, metasomatism, mineralization, and metamorphism in the crust and mantle of the Earth. It comprises the role of halogens in other terrestrial worlds like volatile-rich asteroids, Mars, and the ice moons of Jupiter and Saturn. Review chapters outline and expand upon the basis of our current understanding regarding how halogens contribute to the geochemical/geophysical evolution and stability of terrestrial worlds overall.